Do health infrastructure and services, aging, and environmental quality influence public health expenditures? Empirical evidence from Pakistan. Issue 6 (18th August 2021) - Saleem, Adeel; Cheema, Ahmed Raza; Rahman, Abdul; Ali, Zulfiqar; Parkash, Rajinder
ABSTRACT: Rapidly growing health expenditure is a matter of grave concern for households and governments. Every government is compelled to allocate a sufficient budget to improve people's health. This study, therefore, identifies some major factors that influence the trajectory of public health care expenditure (HCE) in Pakistan for the period 1974–2017. The ARDL-bounds test and Bayer-Hanck cointegration test consistently reveal that HCE and its specified determinants are cointegrated. Long-term estimates show that healthcare infrastructure and services, income, and environmental degradation exert a positive influence on HCE. Elderly population size has a negative association with HCE. Income elasticity is inelastic, showing that healthcare is a necessity. The findings suggest that the government must pay due attention to the fair distribution of health-related infrastructure and personnel in all regions of Pakistan.